Hollow carbon nanosphere one-dimensional functional material modified by contact curvature interface structure as well as preparation method and application of hollow carbon nanosphere one-dimensional functional material

By using hollow carbon nanospheres with a one-dimensional functional material modified with contact curvature interface structure in alkali metal ion batteries, the problem of structural damage in traditional graphite materials during the embedding and removal of sodium and potassium ions is solved, and the storage capacity and cycle stability of high-performance alkali metal ion batteries are achieved.

CN119650694APending Publication Date: 2025-03-18FUJIAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311623853.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional graphite materials will destroy the layered structure during the embedding and removal of sodium and potassium ions, resulting in material peeling, affecting cycle stability, and cannot meet the needs of high-performance alkali metal ion batteries.

Method used

A one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure is used. This material is integrated from a nitrogen-doped porous hollow carbon nanosphere stack, prepared by electrospinning technology and calcining process to form a highly graphitized carbon-based material.

Benefits of technology

The structural stability of graphitized carbon materials and the deintercalation of highly reversible alkali metal ions are achieved, which improves the electron and ion transmission speed, enhances the reaction kinetics, and significantly improves the storage capacity of alkali metal ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650694A_ABST
    Figure CN119650694A_ABST
Patent Text Reader

Abstract

The invention discloses a contact curvature interface structure modified hollow carbon nanosphere one-dimensional functional material and a preparation method and application thereof, and belongs to the technical field of alkali metal ion battery carbon-based negative electrode materials, and the contact curvature interface structure modified hollow carbon nanosphere one-dimensional functional material is formed by stacking and integrating nitrogen-doped porous hollow carbon nanospheres on a one-dimensional carbon material. The preparation method comprises the following steps: by taking a mixed solution of a carbon-forming nitrogen-containing polymer, a metal salt and a one-dimensional carbon material as a raw material, carrying out electrostatic spinning, carbonization, acid etching and carbon dioxide etching on the raw material to obtain the contact curvature interface structure modified hollow carbon nanosphere one-dimensional functional material. The invention also discloses an application of the one-dimensional functional material in an alkali metal ion battery electrode. The product provided by the invention has excellent alkali metal ion storage capacity, and has important application prospects in the field of high-performance alkali metal ion batteries. The method has the advantages of simple and efficient preparation process, easy operation, low cost and the like, and is suitable for further popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon-based negative electrode materials for alkali metal ion batteries, and in particular relates to a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure, and a preparation method and application thereof. Background Art

[0002] Since its commercial application, lithium-ion batteries have dominated the fields of portable energy storage devices, electric vehicles, etc. However, the shortage and uneven distribution of lithium resources have made it impossible to meet the needs of large-scale energy storage in the future. Therefore, it is urgent to find new energy storage devices to replace traditional lithium-ion batteries. Lithium, sodium and potassium are all alkali metal elements, and alkali metal ion batteries have similar electrochemical reaction mechanisms, showing the same "rocking chair" type of charging and discharging. At the same time, in addition to lithium, sodium and potassium elements are abundant in the earth's crust, easier to obtain, and low in cost. Therefore, they have attracted the attention of researchers from all over the world. However, the radius of sodium and potassium ions is larger than that of lithium ions, which causes traditional graphite materials to seriously damage the layered structure of graphite materials during the embedding and extraction of sodium and potassium ions, causing the exfoliation of graphite materials, significantly affecting the cycle stability of graphite, and unable to meet actual application needs.

[0003] The development of high-performance anode materials is the key to the success of alkali metal ion batteries. Among them, carbon-based materials have attracted special attention due to their rich, adjustable microstructures and chemical stability. Graphite, as a successful anode material in lithium-ion batteries, can form a theoretical capacity of 372 mAh g -1 LiC6 intercalation compound. However, people are also pursuing carbon-based negative electrode materials with higher capacity, and the performance of graphite in sodium-potassium ion battery systems is not ideal. In the prior art, in order to solve the above problems, it is proposed to use porous structures and defects to improve the performance of carbon-based negative electrode materials in storing alkali metal ions, or to design the structure of carbon-based materials, such as introducing contact curvature interface design to achieve efficient storage of alkali metals in highly graphitized carbon-based materials.

[0004] Therefore, how to provide an alkali metal ion battery negative electrode material with many interfacial active sites, porous materials, stable structure and good cycle performance is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure, and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A one-dimensional functional material of hollow carbon nanospheres with modified contact curvature interface structure, which is composed of nitrogen-doped porous hollow carbon nanospheres stacked and integrated on a one-dimensional carbon material;

[0008] The Gaussian average curvature of the nitrogen-doped porous hollow nanospheres is 0.01-0.3, and as the number of atoms constituting the carbon nanospheres increases, the corresponding Gaussian average curvature becomes smaller;

[0009] The pore volume of the one-dimensional functional material is 0.5-0.7 cm 3 ·g -1 , outer diameter is 200-300nm, specific surface area is 100-300m 2 ·g -1 .

[0010] Beneficial effects: The present invention prepares a composite one-dimensional carbon fiber material by means of an electrospinning technology combined with a calcination process, and manufactures a unique one-dimensional structure after an acid-based hydrothermal process and carbon dioxide calcination. Specifically, the provided product has high graphitization, and is structurally composed of graphitized nitrogen-doped porous hollow carbon nanospheres wrapped in a stacked and integrated carbon nanotube structure, has a contact curvature interface, and presents a porous hollow structure, which can achieve structural stability of graphitized carbon materials and highly reversible deintercalation of alkali metal ions. Since the contact curvature interface can effectively increase the electron density of carbon-based materials at the Fermi level, it is helpful to increase the adsorption energy of alkali metal ions on carbon negative electrode materials; the one-dimensional functional material provided by the present invention is applied to alkali metal ion electrode materials and assembled into alkali metal ion batteries, which exhibit the characteristics of high specific capacity, good rate performance, strong cycle stability, etc., and have important application prospects in the field of high-performance alkali metal ion batteries.

[0011] A method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure comprises the following steps:

[0012] A mixed solution of a carbon-forming nitrogen-containing polymer, a metal salt and a one-dimensional carbon material is used as a raw material, and after electrostatic spinning, carbonization, acid etching and carbon dioxide etching, the one-dimensional functional hollow carbon nanosphere material with modified contact curvature interface structure is obtained.

[0013] Beneficial effects: The metal salt in the present invention can catalyze graphitization, and the graphitized porous carbon nanosphere / carbon nanotube composite skeleton can not only improve the overall conductivity of the composite electrode material, but also buffer the volume change of the graphitized carbon material during the charge and discharge cycle; the contact curvature interface structure in the composite material accelerates the electron and ion transmission speed, improves the reaction kinetics, and exhibits an outstanding ability to store alkali metal ions.

[0014] Preferably, the mass ratio of the carbon-forming nitrogen-containing polymer to the solvent is (5-20):100;

[0015] The mass ratio of the metal salt, the one-dimensional carbon material and the nitrogen-containing polymer is (100-150):(3-10):100.

[0016] Beneficial effect: The amount of solvent added in the present invention only affects the concentration of the electrospinning solution, and further affects the one-dimensional structure of the electrospun fiber. Those skilled in the art can adjust the amount of solvent added as needed.

[0017] Preferably, the carbon-forming nitrogen-containing polymer includes one or any combination of polyacrylonitrile, polypyrrole, cellulose and polyurethane;

[0018] The metal salt includes one or any combination of cobalt chloride, nickel nitrate, cobalt nitrate and nickel acetate;

[0019] The one-dimensional carbon material includes one or more of nanotubes, hollow carbon nanowires, and carbon nanofibers;

[0020] The solvent of the mixed solution is N,N-dimethylformamide.

[0021] Beneficial effects: The metal salt used in the present invention can catalyze the metal salt outer layer polymer to produce a graphitized carbon layer during the calcination process, and the one-dimensional carbon material serves as the internal skeleton of the graphitized nanospheres, which is beneficial to maintain the one-dimensional structure and can serve as an internal electron pathway to improve the conductivity of the material.

[0022] Preferably, the positive high voltage during the electrospinning process is 21 kV and the spinning rate is 0.8 mL·h -1 , the distance between the nozzle and the collector is 15cm, the ambient humidity is ≤30%, and the rolling speed is 2000r·min -1 .

[0023] Preferably, the carbonization is carried out in a nitrogen atmosphere at a temperature of 700-1000° C. and a time of 2-8 h.

[0024] Preferably, the acid etching is to place the carbonized composite fiber negative electrode precursor in dilute nitric acid for hydrothermal reaction.

[0025] Preferably, the concentration of the dilute nitric acid is 0.5-6 mol / L;

[0026] The temperature of the hydrothermal reaction is 120-180° C., and the time is 5-10 hours.

[0027] Beneficial effect: The nitric acid hydrothermal reaction process directly removes the nickel particles and amorphous carbon, leaving the highly graphitized carbon material.

[0028] Preferably, the temperature of the carbon dioxide etching is 550-950° C., and the time is 0.5-2 h.

[0029] Application of one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure in the preparation of electrode materials for alkali metal ion batteries.

[0030] Preferably, the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure is applied in negative electrode materials of alkali metal ion batteries.

[0031] Compared with the prior art, the present invention has the following advantages and technical effects:

[0032] The one-dimensional functional material of the hollow carbon nanosphere modified by the contact curvature interface structure provided by the present invention can realize the structural stability of the graphitized carbon material and the highly reversible deintercalation of alkali metal ions. Its contact curvature interface structure accelerates the electron and ion transmission speed, improves the reaction kinetics, and shows an outstanding ability to store alkali metal ions, which has important application prospects in the field of high-performance alkali metal ion batteries. The preparation method of the one-dimensional functional material of the hollow carbon nanosphere modified by the contact curvature interface structure provided by the present invention has the advantages of simple and efficient preparation process, easy operation, low cost, etc., and is suitable for further promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0034] Figure 1 This is a SEM image of the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure obtained in Example 1;

[0035] Figure 2 The X-ray diffraction pattern of the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure obtained in Example 1;

[0036] Figure 3 The X-ray photoelectron spectrum of the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure obtained in Example 1;

[0037] Figure 4 The pore size distribution diagram of the one-dimensional functional material of hollow carbon nanospheres modified with the contact curvature interface structure obtained in Example 1;

[0038] Figure 5 The TEM and HRTEM images of the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure obtained in Example 1 are shown in sequence;

[0039] Figure 6 This is the mapping diagram of the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure obtained in Example 1;

[0040] Figure 7 This is a TEM image of the nickel-carbon composite material obtained in Comparative Example 1;

[0041] Figure 8 This is a SEM image of the hollow carbon nanosphere / carbon nanotube composite one-dimensional material obtained in Comparative Example 2;

[0042] Fig. 9 The electrochemical performance diagram of the composite materials obtained in Example 1 and Comparative Examples 1-2 when applied to the negative electrode of an alkali metal ion battery;

[0043] Fig.10 This is a graph showing the results of DFT simulation of the adsorption energy of lithium, sodium and potassium (alkali metal atoms) for Application Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0046] The room temperature in the embodiments of the present invention refers to 25±2°C.

[0047] Example 1

[0048] A method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure comprises the following steps:

[0049] (1) Add 1.0 g of PAN (polyacrylonitrile) and 1.5 g of nickel acetate to 10 mL of DMF and stir to obtain solution A; then add 0.05 g of CNTs powder to 5 mL of DMF and disperse by ultrasonic to obtain solution B; mix solution A and solution B and stir to obtain an electrospinning precursor solution;

[0050] (2) The precursor solution was prepared into a fiber membrane precursor by electrospinning technology, and then the fiber membrane precursor was placed at 60°C for 8 hours for drying; wherein, the positive high voltage during the electrospinning process was 21 kV, and the spinning rate was 0.8 mL·h -1 , the distance between the nozzle and the collector is 15cm, the ambient humidity is ≤30%, and the rolling speed is 2000r·min -1 ;

[0051] (3) The obtained dried fiber membrane precursor was placed in a tube furnace and heated at 5 °C min under a nitrogen atmosphere. -1 The temperature was raised to 700°C at a rate of 1.50 and carbonized for 3 h to obtain a composite carbon nanofiber precursor;

[0052] (4) transferring the composite carbon nanofiber precursor to a hydrothermal reactor containing 25 mL of a 1 mol / L dilute nitric acid solution, reacting at 160° C. for 10 h, and after the reaction is completed, cooling the reactor to room temperature, taking out the carbonized product, and repeatedly washing it three times with anhydrous ethanol to obtain a prefabricated one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure;

[0053] (5) The obtained prefabricated one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure was placed in a tube furnace and heated at 5°C·min under a carbon dioxide atmosphere. -1 The temperature was raised at a rate of , and etching was performed at 550°C for 1 hour. After cooling to room temperature in the furnace, the material was taken out to obtain a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure.

[0054] Figure 1 This is a SEM image of the one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure prepared in Example 1. It can be seen that CNTs are embedded in the hierarchical nanofibers and serve as internal pathways for transmitting electrons;

[0055] Figure 2 The X-ray diffraction diagram of the one-dimensional functional material of the hollow carbon nanosphere modified with the contact curvature interface structure prepared in Example 1 shows that the obtained carbon material is a pure carbon material, the nickel element is removed in the hydrothermal process, and after the carbon dioxide etching process, the material presents multiple defects;

[0056] Figure 3 The X-ray photoelectron spectrum of the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure prepared in Example 1 shows that the material contains nitrogen doping;

[0057] Figure 4 The pore size distribution diagram of the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure prepared in Example 1 shows that the pore structure of the material is mainly dominated by mesopores. According to the test data, the volume of the pores is 0.5-0.7cm 3 ·g -1 , with a specific surface area of ​​100-300m 2 ·g -1 . ;

[0058] Figure 5The TEM and HRTEM images of the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure prepared in Example 1. According to the TEM image, it can be seen that the material is composed of multiple layers of hollow carbon nanospheres in contact and stacking to form fibers, and there are many contact curvature interfaces between the hollow nanospheres. In the HRTEM image, it can be clearly seen that there are many defect sites on the ordered lattice stripes of the carbon matrix. According to simple calculations, the Gaussian average curvature of the hollow carbon sphere is 0.01-0.3, and the Gaussian average curvature changes with the change of the radius of the carbon sphere. Figure 5 The mean curvatures are approximately 0.12, 0.22, and 0.05, corresponding to carbon nanosphere diameters of approximately 15 nm, 45 nm, and 20 nm, respectively.

[0059] Figure 6 Mapping diagram of the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure prepared in Example 1. Figure 6 It can be concluded that the prepared C and N elements are evenly distributed on the carbon fiber.

[0060] Application Example 1

[0061] An alkali metal ion battery, wherein the negative electrode material is prepared by using the one-dimensional functional material of hollow carbon nanospheres modified with the contact curvature interface structure obtained in Example 1, and the preparation method of the alkali metal ion battery comprises the following steps:

[0062] (1) Preparation of negative electrode materials: One-dimensional functional materials of hollow carbon nanospheres modified according to the contact curvature interface structure: conductive carbon black: binder CMC (mass concentration: 10 mg mL -1 )=8:1:1 mass ratio to prepare negative electrode slurry, grind it evenly and apply it on copper foil, then place it in a vacuum drying oven at 70°C for 10 hours, dry it and cut it into circular pole pieces with a diameter of 6 mm to obtain negative electrode pieces for alkali metal ion batteries;

[0063] (2) Assembling alkali metal ion batteries: The prepared negative electrode sheet was used as the working electrode, the lithium sodium potassium metal sheet was used as the counter electrode, Celgard 2400 was used as the separator, and 1.0 mol·L -1 LiPF6, NaPF6 and KFSI solution (the solvent is a mixed solution of EC (ethylene carbonate) and DEC (diethyl carbonate), and the volume ratio of the two is 1:1) is used as the electrolyte to prepare a 2032 button battery.

[0064] The obtained 2032 button cell was subjected to constant current charge and discharge performance test at room temperature. Fig.10 Cyclic performance diagram of one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure prepared in 1, with current density of 1A·g -1When the charge and discharge performance test was carried out, the specific capacity of the lithium sodium potassium ion battery after 1000 cycles reached 320, 235 and 190 mAh g -1 %.

[0065] Example 2

[0066] A method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure comprises the following steps:

[0067] (1) Add 1.0 g of PAN and 1.5 g of cobalt acetate to 10 mL of DMF and stir to obtain solution A; add 0.05 g of hollow carbon fiber powder to 5 mL of DMF and disperse by ultrasonic to obtain solution B; mix solution A and solution B and stir to obtain an electrospinning precursor solution;

[0068] (2) The precursor solution was prepared into a fiber membrane precursor by electrospinning technology, and then the fiber membrane precursor was placed at 60°C for 8 hours for drying; wherein, the positive high voltage during the electrospinning process was 21 kV, and the spinning rate was 0.8 mL·h -1 , the distance between the nozzle and the collector is 15cm, the ambient humidity is ≤30%, and the rolling speed is 2000r·min -1 ;

[0069] (3) The obtained dried fiber membrane precursor was placed in a tube furnace and heated at 5 °C min under a nitrogen atmosphere. -1 The temperature was raised to 750°C and carbonized for 4 h to obtain a composite carbon nanofiber precursor;

[0070] (4) transferring the composite carbon nanofiber precursor to a hydrothermal reactor containing 25 mL of a 0.5 mol / L dilute nitric acid solution, reacting at 160° C. for 10 h, taking out the reactor after cooling, and repeatedly washing it with anhydrous ethanol three times to obtain a prefabricated one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure;

[0071] (5) The prefabricated one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure was placed in a tube furnace and heated at 5°C min under a carbon dioxide atmosphere. -1 The temperature was raised at a rate of , and etching was performed at 600°C for 1 hour. After cooling to room temperature in the furnace, the material was taken out to obtain a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure.

[0072] Example 3

[0073] A method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure comprises the following steps:

[0074] (1) Add 1.0 g of PAN and 1.5 g of nickel acetate to 10 mL of DMF and stir to obtain solution A; add 0.08 g of carbon nanofiber powder to 5 mL of DMF and disperse by ultrasonic to obtain solution B; mix solution A and solution B and stir to obtain an electrospinning precursor solution;

[0075] (2) The precursor solution was prepared into a fiber membrane precursor by electrospinning technology, and then the fiber membrane precursor was placed at 60°C for 8 hours for drying. The positive high voltage during the electrospinning process was 21 kV and the spinning rate was 0.8 mL·h -1 , the distance between the nozzle and the collector is 15cm, the ambient humidity is ≤30%, and the rolling speed is 2000r·min -1 ;

[0076] (3) The obtained dried fiber membrane precursor was placed in a tube furnace and heated at 5 °C min under a nitrogen atmosphere. -1 The temperature was raised to 700°C at a rate of 1.50 and carbonized for 3 h to obtain a composite carbon nanofiber precursor;

[0077] (4) transferring the composite carbon nanofiber precursor to a hydrothermal reactor containing 25 mL of a 2 mol / L dilute nitric acid solution, reacting at 160° C. for 10 h, taking out the reactor after cooling, and repeatedly washing it with anhydrous ethanol three times to obtain a prefabricated one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure;

[0078] (5) The prefabricated one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure was placed in a tube furnace and heated at 5°C min under a carbon dioxide atmosphere. -1 The temperature was raised at a rate of , etched at 700°C for 1 hour, and taken out after cooling to room temperature in the furnace to obtain a one-dimensional material of porous hollow nitrogen-doped carbon nanospheres integrated with a contact curvature interface structure modified.

[0079] Comparative Example 1

[0080] A method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure, which is different from Example 1 in that the nitric acid hydrothermal process in step (4) is not included and Ni particles are not removed to obtain a Ni / nitrogen-doped carbon nanofiber composite material.

[0081] Depend on Figure 7 It can be seen from the TEM image that the structure of the Ni / nitrogen-doped carbon nanofiber composite material is different from the one-dimensional material of the porous hollow nitrogen-doped carbon nanospheres integrated with the contact curvature interface structure modified in the present invention. The composite material obtained in Comparative Example 1 was prepared into a negative electrode according to the method in Application Example 1, and lithium, sodium and potassium ion batteries were assembled for performance testing. The voltage range was 0 to 3 V. The cycle and rate modes were used. When the current density was 1 A·g-1 When the charge and discharge performance test was carried out, the specific capacities of lithium, sodium and potassium ion batteries after 1000 cycles were 205, 130 and 80 mAh g respectively. -1 , cycle performance diagram see Fig. 9 .

[0082] Comparative Example 2

[0083] A method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure is different from that of Example 1 in that step (5) is not included, that is, a carbon dioxide etching process is not included.

[0084] Figure 8 The SEM image of the one-dimensional composite material of hollow carbon nanosphere / carbon nanotube can be seen. The carbon-based graphite in the composite material obtained in Comparative Example 2 can be seen. The composite material obtained in Comparative Example 2 is used to prepare a negative electrode according to the method in Application Example 1, and lithium, sodium and potassium ion batteries are assembled for performance testing. The voltage range is 0 to 3 V. The cycle and rate modes are used. When the current density is 1 A·g -1 When the charge and discharge performance test was carried out, the specific capacities of lithium, sodium and potassium ion batteries after 1000 cycles were 276, 173 and 150 mAh g -1 , cycle performance diagram see Fig. 9 .

[0085] Fig.10 This is a DFT simulation comparison diagram of Example 1 and Comparative Examples 1-2. From the figure, it can be seen that the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure prepared in Example has much greater adsorption capacity for lithium, sodium and potassium than Comparative Examples 1-2.

[0086] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure, characterized in that: It is composed of nitrogen-doped porous hollow carbon nanospheres stacked and integrated on a one-dimensional carbon material; The Gaussian average curvature of the nitrogen-doped porous hollow nanospheres is 0.01-0.3; The pore volume of the one-dimensional functional material is 0.5-0.7 cm 3 ·g -1 , outer diameter is 200-300nm, specific surface area is 100-300m 2 ·g -1 .

2. The method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure according to claim 1, characterized in that: The steps include: A mixed solution of a carbon-forming nitrogen-containing polymer, a metal salt and a one-dimensional carbon material is used as a raw material, and after electrostatic spinning, carbonization, acid etching and carbon dioxide etching, the one-dimensional functional hollow carbon nanosphere material with modified contact curvature interface structure is obtained.

3. The method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure according to claim 2, characterized in that: The mass ratio of the carbon-forming nitrogen-containing polymer to the solvent is (5-20):100; The mass ratio of the metal salt, the one-dimensional carbon material and the nitrogen-containing polymer is (100-150):(3-10):

100.

4. The method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure according to claim 3, characterized in that: The carbon-forming nitrogen-containing polymer includes one or any combination of polyacrylonitrile, polypyrrole, cellulose and polyurethane; The metal salt includes one or any combination of cobalt chloride, nickel nitrate, cobalt nitrate and nickel acetate; The one-dimensional carbon material includes one or more of nanotubes, hollow carbon nanowires, and carbon nanofibers; The solvent of the mixed solution is N,N-dimethylformamide.

5. The method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure according to claim 2, characterized in that: The carbonization is carried out in a nitrogen atmosphere at a temperature of 700-1000° C. and a time of 2-8 hours.

6. The method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure according to claim 2, characterized in that: The acid etching is to place the carbonized composite fiber negative electrode precursor in dilute nitric acid for hydrothermal reaction.

7. The method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure according to claim 6, characterized in that: The concentration of the dilute nitric acid is 0.5-6 mol / L; The temperature of the hydrothermal reaction is 120-180° C., and the time is 5-10 hours.

8. The method for preparing a one-dimensional functional material of hollow carbon nanospheres modified with a contact curvature interface structure according to claim 2, characterized in that: The temperature of the carbon dioxide etching is 550-950° C., and the time is 0.5-2 h.

9. Use of the one-dimensional functional material of hollow carbon nanospheres modified with contact curvature interface structure as claimed in claim 1 in the preparation of electrode materials for alkali metal ion batteries.